Tennessee Williams and the Hollywood Film - Dragon, Zoltán (FOCUS: Papers in English Literary and Cultural Studies, 2024)
A Strange skeleton appears in the film version of Suddenly Last Summer (directed by Joseph L. Mankiewicz, adapted from the drama by Williams himself with the help of Gore Vidal). This skeleton is not present in the “source text,” and its filmic presence can be regarded as a kind of manifestation of lack: nobody notices it, even though it appears at significant places and in significant moments. Moreover, in an environment that is evidently heterogeneous to its existence, it is obviously “out of place.” It becomes an uncanny presence that may even be seen as an insignificant problem; however, it subverts both the mechanism of representation in the film and the general and canonized views concerning the discourse of the adaptation of drama to film. The adaptation of drama to film is, for most critics, absolutely unproblematic, or even self-evident and “natural” (Hayward 4).